On the heterogenous trade and welfare effects of GATT/WTO membership - Gabriel Felbermayr; Mario Larch; Erdal Yalçin; Yoto Yotov (FIW - Research Centre International Economics, 2022)
We quantify the partial and general equilibrium effects of GATT/WTO membership on trade and welfare. Using an extensive database covering manufacturing trade for 186 countries over the period 1980-2016, we find that the average impact of GATT/WTO membership on trade among member counties is large, positive, and significant. We contribute to the literature by estimating country-specific estimates and find them to vary widely across the countries in our sample with poorer members benefitting more. Using these estimates, we simulate the general equilibrium effects of GATT/WTO on welfare, which are sizable and heterogeneous across members, and relatively small for non-member countries. We show that countries not experiencing positive trade effects from joining GATT/WTO can still gain in terms of welfare, due to lower import prices and higher export demand.
Keywords: F1; F13; F14; 330; GATT; WTO; Heterogenous Policy Effects; Welfare